EFFECTS OF BULLWHIP ON SUPPLY CHAIN PERFORMANCE IN MANUFACTURING SECTOR IN KENYA, A CASE OF COOPER K BRANDS LIMITED - Njuguna, Julius kuria; Ismael, Dr. Noor (International Journal of Supply Chain Management, 2017)
Purpose: This study focused to analyzing the effect of bullwhip on supply chain performance in manufacturing sector in Kenya. The specific objectives of the study were: to establish the effect of demand forecasting, production strategies, rationing game, and information sharing on supply chain Performance in the manufacturing sector in Kenya Materials and Methods: The study adopted a descriptive study approach. The total population of the study was all employees working at Coopers Kenya limited. The company had a total of one hundred and eighty (180) employees who are involved in the operations of the company. The target population was individuals which the researcher was interested in describing and making statistical inferences about. Therefore the target population was one hundred and eighty (180) employees working at CKL. Simple Random sampling method was used to select the one hundred and twenty four (124) respondents. This research applied both primary and secondary data. Pilot study was conducted by providing the questionnaires to 10% of the sample size. The collected data was analyzed through descriptive statistics and inferential statistics. Data presentation was through the use of pie charts, bar charts, graphs and frequency tables. Correlation analysis was used to establish the relationship between the independent and dependent variables. Results: The study found that demand forecasting, production strategies, rationing game, and information sharing were factors affecting supply chain Performance in the manufacturing sector in Kenya. Recommendations: The study recommended that organization should adopt modern methods and techniques of forecasting demand which will enhance the accuracy of the forecast demand, the use of production smoothing strategies which will results to consistency in the production levels irrespective of the variation of demands, study therefore recommends the elimination of order rationing strategy as a means of managing shortages in the supply chain and the organizations to fully embrace the use of modern information technology in order to enhance information flow.